INSTRUCTION IN METHODS OF ACCOUNTING CONTROL: A SYMPOSIUM. - Heckert, J. B. (The Accounting Review, 1937)
Abstract A very large proportion of those students who do their major work in accounting in colleges and universities ultimately find their way into the accounting departments of industrial, commercial and financial concerns. Many others are ultimately engaged in production, sales and financial activities to which accounting and statistical analysis has a close relationship. In successful training of this group there devolves upon instructional staffs, an important responsibility for training not only in accounting principles but also in methods of collection and use of accounting and statistical data for managerial control purposes. With the importance of this phase of accounting instruction in mind, a round-table discussion was organized at the annual meeting of the American Accounting Association in December 1936, at which representatives of numerous schools were asked to make brief statements pertaining to methods used in their institutions. The author emphasizes on internal control in accounting courses.